Evaluation of timed barium esophagram after per-oral endoscopic myotomy to predict clinical response - John M. DeWitt (Georg Thieme Verlag KG, 2021)
Background and study aims The aim of this study was to evaluate whether timed barium esophagram within 24 hours post-per-oral endoscopic myotomy (POEM) (TBE-PP) could predict clinical outcomes. Patients and methods This was a single-center retrospective study of prospectively collected data on consecutive patients with ≥ 6-month follow-up who underwent POEM followed by TBE-PP. Esophageal contrast retention 2 minutes after TBE-PP was assessed as Grade 1 (< 10 %), 2 (10 %–49 %), 3 (50 %–89 %) or 4 (> 90 %). Eckardt score, esophagogastroduodenoscopy (EGD), high-resolution manometry (HRM) and function lumen imaging probe (FLIP) of the esophagogastric junction (EGJ) were obtained at baseline. These tests along with pH testing of antisecretory therapy were repeated 6 and 24 months after POEM. Clinical response by Eckardt score ≤ 3, EGJ-distensibility index (EGJ-DI) > 2.8 mm2/mm Hg, and integrated relaxation pressure (IRP) < 15 mm Hg and incidence of gastroesophageal reflux disease (GERD) were compared by transit time. Results Of 181 patients (58 % male, mean 53 ± 17 yr), TBE-PP was classified as Grade 1 in 122 (67.4 %), Grade 2 in 41 (22.7 %), Grade 3 in 14 (7.7 %) and Grade 4 in 4 (2.2 %). At 6 months, overall clinical response by ES (91.7 %), IRP (86.6 %), EGJ-DI (95.7 %) and the diagnosis of GERD (68.6 %) was similar between Grade 1 and Grade 2–4 TBE-PP. At 24 months, Grade 1 had a higher frequency of a normal IRP compared to Grades 2–4 (95.7 % vs. 60 %, P = 0.021) but overall response by ES (91.2 %), EGJ-DI (92.3 %) and the diagnosis of GERD (74.3 %) were similar. Conclusions Contrast emptying rate by esophagram after POEM has limited utility to predict clinical response or risk of post-procedure GERD.